PEMBERIAN KOMPOS KULIT BUAH KAKAO PADA TANAMAN KELAPA SAWIT (Elaeis guineensis Jacq.) BELUM MENGHASILKAN UMUR 2 TAHUN DI KEBUN SAWIT FAKULTAS PERTANIAN UNIVERSITAS RIAU - Roy Tenson; Sampurno Sampurno; Idwar Idwar (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
This study aimed to determine the effect of pod husks compost on plant growth of oil palm (Elaeis guineensis Jacq.) Has not produced the age of 2 years as well as to get the best dose for the growth of palm trees age of 2 years. This study was conducted over five months, namely from March 2015 to July 2016. The research was conducted in the garden of palm Faculty of Agriculture, University of Riau Campus Bina Widya Km 12.5 Baru Simpang Village, District Handsome, Pekanbaru. This study uses a randomized complete block design (RAK) non factorial consisting of six treatment that without treatment; Award KKBK 3.67 kg/plant; Award KKBK 7.35 kg/plant; Award KKBK 11.1 kg/plant; Award KKBK 14.7 kg/plant; Award KKBK 18.3 kg/plant and each treatment was repeated 3 times so that each experimental unit obtained 18 experimental units. The parameters measured were the increase of plant height, girth increase, the increase of the length midrib and leaf child. Based on the results of research to get the growth of oil palm plantations tend to be better at giving compost pod husks dose of 18.3 kg / plant. Keywords:Palm Oil, compost, cocoa Fruit Leather